Development of a Modular Automated System for Maintenance and Differentiation of Adherent Human Pluripotent Stem Cells. (September 2017) - Crombie, Duncan E.; Daniszewski, Maciej; Liang, Helena H.; Kulkarni, Tejal; Li, Fan; Lidgerwood, Grace E.; Conquest, Alison; Hernández, Damian; Hung, Sandy S.; Gill, Katherine P.; De Smit, Elisabeth; Kearns, Lisa S.; et al.
Patient-specific induced pluripotent stem cells (iPSCs) have tremendous potential for development of regenerative medicine, disease modeling, and drug discovery. However, the processes of reprogramming, maintenance, and differentiation are labor intensive and subject to intertechnician variability. To address these issues, we established and optimized protocols to allow for the automated maintenance of reprogrammed somatic cells into iPSCs to enable the large-scale culture and passaging of human pluripotent stem cells (PSCs) using a customized TECAN Freedom EVO. Generation of iPSCs was performed offline by nucleofection followed by selection of TRA-1-60–positive cells using a Miltenyi MultiMACS24 Separator. Pluripotency markers were assessed to confirm pluripotency of the generated iPSCs. Passaging was performed using an enzyme-free dissociation method. Proof of concept of differentiation was obtained by differentiating human PSCs into cells of the retinal lineage. Key advantages of this automated approach are the ability to increase sample size, reduce variability during reprogramming or differentiation, and enable medium- to high-throughput analysis of human PSCs and derivatives. These techniques will become increasingly important with the emergence of clinical trials using stem cells.